2009
DOI: 10.1186/1752-0509-3-33
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of metabolic pathways for the cattle genome

Abstract: Background: Metabolic reconstruction of microbial, plant and animal genomes is a necessary step toward understanding the evolutionary origins of metabolism and species-specific adaptive traits. The aims of this study were to reconstruct conserved metabolic pathways in the cattle genome and to identify metabolic pathways with missing genes and proteins. The MetaCyc database and PathwayTools software suite were chosen for this work because they are widely used and easy to implement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 86 publications
0
46
0
2
Order By: Relevance
“…Metabolic reconstruction or reconstruction of metabolic pathways of a genome is a process of linking known enzymatic reactions and pathways to annotated genes of the genome (Seo and Lewin, 2009). There have been many attempts to reconstruct metabolic pathways for a wide variety of organisms, and various bioinformatic tools are available for reconstructing metabolic pathways automatically (see the review by Pitkä nen et al (2010)).…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…Metabolic reconstruction or reconstruction of metabolic pathways of a genome is a process of linking known enzymatic reactions and pathways to annotated genes of the genome (Seo and Lewin, 2009). There have been many attempts to reconstruct metabolic pathways for a wide variety of organisms, and various bioinformatic tools are available for reconstructing metabolic pathways automatically (see the review by Pitkä nen et al (2010)).…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%
“…For example, Seo and Lewin (2009) found that 53% of pathways in the initial automated reconstruction for cattle needed to be deleted or modified, and manually modified or created 66 mammalian-specific metabolic pathways from the reference pathways in MetaCyc. Accumulated knownledge about mammalian enzymatic reactions and metabolic pathways and deposition of these information in biological databases (e.g.…”
Section: Linking Cattle Genome To Ruminant Metabolismmentioning
confidence: 99%
See 3 more Smart Citations